Heritage Conservation and Restoration in Puno: Report on a Professional Visit - Dion, Vincent (2022)
In June 2022 the author, a conservator-restorer of cultural heritage based in Canada, travelled to the region of Puno for a professional visit to develop expertise in the conservation of at-risk heritage.